The impact of public assisted contract farming programmes in Malaysia - Kaur, Bisant; Kamarulzaman, Nitty Hirawaty; Hamzah, Nur Amalina (Federal Agricultural Marketing Authority (FAMA), 2015)
Under the Ninth Malaysia Plan (9MP), contract farming was introduced as a high-impact project under the Ministry of Agriculture and Agro-based Industry (MoA) to revitalise the agricultural sector as Malaysia's third pillar of economic growth. The programme had the objectives of providing assured markets and of increasing producers' incomes. Eight departments/agencies under the MoA were given the responsibility to provide assistance and facilitate farmers to ensure the success of the contract-farming programme. The objective of this study was to evaluate the contract farming programme to determine whether it had fulfilled its objectives in terms of production, number of farmers involved, and incomes of farmers. Face-to-face interviews using semi-structured questionnaires were carried out with 107 contract farmer located in the states of Kelantan, Terengganu, Selangor, Johor and Perak. This study revealed that the contract farming programme had improved the production of agricultural products and increased farmers' average total incomes after five years. It was also found that after involvement with the contract farming programme, majority of the farmers marketed their entire produce through the Federal Agricultural Marketing Authority (FAMA).